Concept Mapping to Enhance Critical Thinking in Nursing Students (International Journal of Nursing Education, 2022)
Background: Teaching strategies are embraced to engage and support students in learning and realizingthe potential through the guiding tools. Concept mapping is an innovative and effective strategy tofacilitate meaningful learning and promote critical thinking among nursing students.Material: Concept map is a learning tool as it links concepts and sub-concepts in a diagrammaticmanner. This teaching strategy encourages in-depth learning of concepts, better comprehension, andcorrelation in clinical practice. This leads to enhanced critical thinking and improved decision making.Conclusion: Concept mapping is a new pedagogical approach that can be used to developed students’critical thinking skills. However, it means development of higher-order reasoning and cognitive skills.